Primordial gravitational waves from spontaneous Lorentz symmetry breaking - Mohsen Khodadi; Gaetano Lambiase; Leonardo Mastrototaro; Tanmay Kumar Poddar (Physics Letters B)
We study the effect of Spontaneous Lorentz Symmetry Breaking (SLSB) on Primordial Gravitational Waves (PGWs) generated during inflation. The SLSB is induced by a time-like Bumblebee vector field which is non-minimally coupled to the Ricci tensor in the Friedmann-Lemaître-Robertson-Walker background. The power spectrum and GW amplitude are computed to investigate how Lorentz violation leaves observable imprints. We calculate the GW strain amplitude over frequencies (10−10Hz,104Hz), for a range of the dimensionless Lorentz-violating parameter, −10−3≤l≤10−4, which essentially comes from a slight sensitivity to the equation of state for dark energy. For positive l values, the amplitude of GW shows a mild suppression compared to the standard cosmological scenario (l=0). This effect could be observable with detectors like SKA, μ-Ares, and BBO. Conversely, negative l values amplify the GW amplitude, enhancing detectability by both SKA, μ-Ares, and BBO, as well as by THEIA and DECIGO. Notably, the GW strain amplitude increases by an order of magnitude as l moves from 0 to −10−3, improving prospects for detection in high-sensitivity detectors like THEIA and DECIGO.